(untitled) (Clinical Sociology Review, 2024)
This article presents an epistemological reflection on the clinical posture in social sciences and the relationship to the object in a thesis project where the student is situated in a dual posture of proximity and distance. As a speaker, immigrant mother and doctoral student wishing to better understand the transcultural encounter between speakers and immigrant parents, the author takes you into her reflection on the relevant modalities that can promote the realization of an objectification process in clinical research in social sciences. The objective of the presentation of this reflexivity is to provide other student-researchers, situated in a dual posture, with avenues of reflection to develop a frame of reference allowing them to move towards objectification. The author thus hopes to contribute to transforming the perception of subjectivity, considered as an obstacle to a lever in the construction of scientific knowledge. First, she presents the broad outlines of her thesis project as well as her clinical posture in research, including her epistemological positioning and her methodological choices. She will then present her reflexivity by answering the question "Who am I?" in order to better understand her relationships with the research object. Finally, she will propose some of the fundamental principles and tools that can be available to student-researchers wishing to progress towards objectification while reducing the tension likely to arise between proximity and distancing from the research object.